Low-lithium high-strength transparent microcrystalline glass and preparation method thereof
Through the use of low -lithium -lithium content raw materials and reasonable process measures during the preparation of microcrystalline glass, it solves the problem of insufficient refined and high production costs, and realizes the preparation of low -lithium high -strength transparent microcrystalline glass. With high transparency and good mechanical properties, it reduces production costs and extends the service life of glass kiln.
Patent Information
- Application Number
- CN202411412896.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-24
AI Technical Summary
The crystallization control of existing microcrystalline glass is not accurate enough during the preparation process, resulting in a decrease in light transmittance, an increase in haze and even loss of transparency. At the same time, its production cost is higher than that of traditional cover glass, and lithium is in high temperature environments. Increased element content will accelerate reaction rate and refractory loss.
The raw material ratio with low lithium content, including li2O: 7WT % ~ 15WT %, Al2O3: 2WT % ~ 12WT %, SIO2: 60WT % ~ 78WT %, ZRO2: 1WT % ~ 4WT %, P2O5: 1WT % ~ 5WT %, NA2O: 0 ~ 1wt %, K2O: 0 ~ 3WT %; SB2O3: 0WT % ~ 0.6WT %. Through reasonable component design and process system, the use of lithium carbonate raw materials is reduced. As the main crystal phase, a uniform crystal distribution is achieved by the buried process.
Realize the preparation of low -lithium, high -strength transparent microcrystalline glass, have high transparency, high -resistant crack expansion and falling mechanical properties, good processing performance, reduce production costs, extend the service life of glass kiln, and improve the materials of the material Market value.
Smart Images

Figure CN119349885A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of glass and relates to microcrystalline glass, and in particular to a low-lithium high-strength transparent microcrystalline glass and a preparation method thereof. Background Art
[0002] Glass-ceramics is a polycrystalline material made from basic glass through controlled crystallization. It is a polycrystalline material with uniform glass and crystals formed by adding nucleating agents to the original glass components and performing heat treatment. Therefore, it is also called glass ceramics. Compared with ordinary glass, glass-ceramics has high light transmittance, high mechanical properties such as high resistance to crack propagation and drop, and good processing performance.
[0003] Based on the above advantages, microcrystalline glass is usually applied to the field of mobile display device cover glass with high strength requirements. However, as an advanced material, the application of microcrystalline glass on smartphone cover plates started late, but its unique potential cannot be ignored. The control of crystallization in the preparation process of microcrystalline glass has become a technical challenge. If the crystallization process is not accurately regulated, it is very easy to cause a decrease in transmittance, an increase in haze, and even a serious problem of loss of transparency. This is undoubtedly a fatal defect for the application of cover glass that pursues extreme transmittance. In addition, from a cost perspective, the production cost of microcrystalline glass is much higher than that of traditional cover glass. Preliminary estimates show that the production cost of microcrystalline glass per ton is likely to account for up to RMB 100,000 in lithium carbonate raw materials alone. This cost is significantly higher than the production cost of traditional cover glass by several times, posing a severe challenge to the manufacturer's cost management capabilities. In addition, in a high-temperature production environment, the increase in lithium content will cause the reaction rate to accelerate sharply. Although this can enhance the reaction efficiency, it also accelerates the loss of refractory materials and reduces the durability of the glass production line. This change may not only affect the stable output and quality assurance of glass products, but may also increase operating costs due to the indirect increase in energy consumption, and the entire production process will therefore face more variables and potential risks. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a low-lithium high-strength transparent microcrystalline glass and a preparation method thereof. The prepared microcrystalline glass has high transparency, high mechanical properties against crack propagation and falling, good processing properties, and a low lithium content. It has a good market value and plays a positive role in extending the life of the glass kiln.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A low-lithium high-strength transparent microcrystalline glass, the raw materials of which include: Li2O: 7wt%~15wt%, Al2O3: 2wt%~12wt%, SiO2: 60wt%~78wt%, ZrO2: 1wt%~4wt%, P2O5: 1wt%~5wt%, Na2O: 0~1wt%, K2O: 0~3wt%; Sb2O3: 0wt%~0.6wt%.
[0007] The present invention also has the following technical features:
[0008] Preferably, the components Na2O+K2O in the raw material>0.5wt%.
[0009] Preferably, the raw material component Li2O accounts for 7wt% to 13wt%, Al2O3 accounts for 5wt% to 8wt%, and SiO2 accounts for 70wt% to 78wt%.
[0010] Preferably, the components P2O5+ZrO2 in the raw material are less than 7wt%.
[0011] Preferably, for a sample with a thickness of 1 to 2 mm, the transmittance is at least 88% within the wavelength range of 450 nm to 800 nm.
[0012] Preferably, for samples with a thickness of 1 to 2 mm, the haze is no greater than 0.3%.
[0013] Preferably, the crystallinity is greater than 85%, and the Vickers hardness is greater than or equal to 840 kgf / mm 2 , elastic modulus ≥ 100GPa, fracture toughness ≥ 1.1MPa·m 1 / 2 .
[0014] The present invention also protects a method for preparing the low-lithium high-strength transparent microcrystalline glass as described above, comprising the following steps:
[0015] Step 1: weigh all raw materials for melting transparent glass-ceramics according to mass ratio and mix them evenly;
[0016] Step 2: Put the mixed material obtained in step 1 into a platinum crucible, heat and melt it in a muffle furnace, and after it is fully melted and clarified, pour the obtained melt into an iron mold, then transfer it to an annealing furnace for annealing treatment and cool it with the furnace, and the obtained basic glass sample is stored and used for standby;
[0017] Step 3: Grind part of the sample in step 2 into powder, perform DSC test, and obtain the crystallization temperature;
[0018] Step 4: Place the base glass from step 2 in a furnace, cover it with alumina or silica powder for crystallization, and after the crystallization is completed, cool it to room temperature with the furnace to obtain high-strength transparent microcrystalline glass.
[0019] Preferably, the melting temperature in step 2 is set to 1450° C. and the melting time is set to 2 h;
[0020] The annealing temperature is 520° C. and the annealing time is 30 minutes.
[0021] Preferably, the crystallization process described in step 4 is: crystallization treatment at a temperature of 550° C. for 60 minutes, and then crystallization treatment at a temperature of 620° C. for 120 minutes.
[0022] Compared with the prior art, the present invention has the following technical effects:
[0023] The low-lithium high-strength transparent microcrystalline glass of the present invention comprises a first crystal phase and a second crystal phase; the first crystal phase is a lithium silicate crystal phase, the lithium silicate crystal phase accounts for ≥65% of the mass percentage of the microcrystalline glass, the lithium silicate crystal phase is a lithium disilicate crystal phase or a lithium metasilicate crystal phase, wherein the total content of lithium disilicate has a higher mass percentage than other crystal phases; the second crystal phase is petalite; the lithium disilicate crystal phase has a higher mass percentage, so that the intrinsic strength and transparency of the microcrystalline glass are improved, thereby forming a microcrystalline glass product with high mechanical strength, high transmittance, low haze, low dielectric loss and high thermal conductivity, which can meet the requirements of mobile phone cover glass for microcrystalline glass, reduce costs and have good market value, and the high-strength transparent microcrystalline glass of the present invention can be applied to the front cover and / or rear cover protection components in the cover material for touch display products;
[0024] Lithium disilicate (Li2Si2O5) is used as the core crystal phase. The crystal is evenly distributed in the glass matrix to construct a unique tetrahedral array of corrugated orthorhombic crystal structure. These crystals are closely connected in an irregular hinge mode to form a complex network structure. When encountering external impact, cracks tend to spread along the complex paths in these crystal networks, and this interlocking microstructure can effectively limit the rapid expansion of cracks, thereby significantly improving the glass's resistance to falling ball impact and its fracture toughness. In addition, the optical refractive properties of lithium disilicate show a high degree of compatibility with the glass matrix, ensuring the excellent performance of the overall material in optical properties and giving this type of glass excellent light transmittance, which has a significant advantage in improving the visual experience of mobile phone displays; on the other hand, petalite (LiAlSi4O 10 ) is a monoclinic crystal with a unique three-dimensional framework consisting of folded Si2O5 layers connected by Li and Al tetrahedra, showing excellent thermal stability; compared with β-spodumene, petalite exhibits an extremely low thermal expansion coefficient in the high temperature range (α20-600℃=0.3×10 -6 / ℃), so that the glass with it as the main crystal phase can withstand higher thermal shock without being easily broken; in addition, during the strengthening process of the cover glass, the Li element in the petalite structure can be partially replaced by Na or K in the solution. This chemical replacement process further improves the strengthening effect of the glass and enhances its overall performance.
[0025] In order to make the lithium disilicate crystal phase have a higher mass proportion, the present invention reduces the use of lithium carbonate raw materials as much as possible while ensuring the proportion of lithium silicate crystal phase in the microcrystalline glass through reasonable component design and process system, effectively saving costs and extending the service life of the glass kiln; the crystallization process adopts the buried firing process, so that the base glass is heated evenly, which can make the high-strength lithium aluminum silicon transparent microcrystalline glass of the present invention have a suitable grain size and uniform distribution, so that the microcrystalline glass of the present invention has excellent mechanical properties and transparency. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope image of the glass-ceramics obtained in Example 3 after corrosion;
[0027] Figure 2 The differential scanning calorimetry (DSC) curve of the glass-ceramics obtained in Example 3;
[0028] Figure 3 This is a visible light transmittance analysis diagram of the glass-ceramics obtained in Examples 1-5;
[0029] Figure 4 Thermal expansion curve of glass-ceramics obtained in Example 3;
[0030] Figure 5 XRD patterns of glass-ceramics obtained in Examples 1-5;
[0031] Figure 6 The Raman spectra of the base glasses of Examples 1-5 are shown in FIG. DETAILED DESCRIPTION
[0032] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0033] Example 1
[0034] This embodiment provides a method for preparing a high-strength transparent microcrystalline glass, comprising the following steps:
[0035] S1, preparing a microcrystalline precursor glass composition:
[0036] Mix Li2O: 7wt%; Al2O3: 7.85wt%; SiO2: 78wt%; ZrO2: 4wt%; P2O5: 2.25wt%; Na2O: 0.15wt%; K2O: 0.15wt%; Sb2O3: 0.6wt% evenly;
[0037] S2, melting the glass raw materials obtained in S1 at high temperature;
[0038] The obtained mixed material is placed in a platinum crucible and heated and melted in a muffle furnace; the melting temperature is 1450°C and the melting time is 120 minutes. After it is fully melted and clarified, the obtained melt is poured into an iron mold, and then transferred to an annealing furnace for annealing treatment and then cooled with the furnace; the annealing temperature is 520°C and the annealing time is 30 minutes; the obtained basic glass sample is stored and used for later use;
[0039] S3, take a small amount of the base glass obtained in S2 and grind it into powder in an agate mortar, pass it through a 100-mesh sieve, and take an appropriate amount of the powder for DSC testing;
[0040] S4, crystallizing the base glass obtained in S2 according to the differential thermal measurement data obtained in S3 and related information;
[0041] 1) Heat the base glass to the nucleation temperature (T N ), and maintaining the predetermined time (tc) at the nucleation temperature to obtain the nucleated base glass; wherein the heating rate is preferably 10°C / min, the predetermined time is preferably 60min, and the nucleation temperature is preferably 550°C;
[0042] 2) heating the nucleated base glass obtained in step 1) to a crystallization temperature (Tc), and maintaining the base glass at the crystallization temperature for a predetermined time to obtain a crystallized base glass; wherein the heating rate is preferably 10°C / min, the predetermined time is preferably 120min, and the crystallization temperature is preferably 600-630°C;
[0043] 3) Cooling the crystallized base glass obtained in step 2) to room temperature at a certain cooling rate to obtain a transparent microcrystalline glass, wherein the crystallinity of the obtained microcrystalline glass is ≥85%, and the crystal phase of the microcrystalline glass is lithium silicate and petalite crystal phase; when the thickness of the microcrystalline glass is 1 to 2 mm, it has a transmittance of ≥88% for light in the wavelength range of 450nm to 800nm.
[0044] Example 2
[0045] Example 2 is basically the same as Example 1, except that the raw materials include: Li2O: 9wt%; Al2O3: 7.85wt%; SiO2: 76wt%; ZrO2: 4wt%; P2O5: 2.25wt%; Na2O: 0.15wt%; K2O: 0.15wt%; Sb2O3: 0.6wt%.
[0046] Example 3
[0047] Example 3 is basically the same as Example 1, except that the raw materials include: Li2O: 11wt%; Al2O3: 7.85wt%; SiO2: 74wt%; ZrO2: 4wt%; P2O5: 2.25wt%; Na2O: 0.15wt%; K2O: 0.15wt%; Sb2O3: 0.6wt%.
[0048] Example 4
[0049] Example 4 is basically the same as Example 1, except that the raw materials include: Li2O: 13wt%; Al2O3: 7.85wt%; SiO2: 72wt%; ZrO2: 4wt%; P2O5: 2.25wt%; Na2O: 0.15wt%; K2O: 0.15wt%; Sb2O3: 0.6wt%.
[0050] Example 5
[0051] Example 5 is basically the same as Example 1, except that the raw materials include: Li2O: 15wt%; Al2O3: 7.85wt%; SiO2: 70wt%; ZrO2: 4wt%; P2O5: 2.25wt%; Na2O: 0.15wt%; K2O: 0.15wt%; Sb2O3: 0.6wt%.
[0052] Example 6
[0053] Example 6 is basically the same as Example 1, except that the raw materials include: Li2O: 10.04wt%; Al2O3: 6wt%; SiO2: 78wt%; ZrO2: 1wt%; P2O5: 1wt%; Na2O: 3wt%; K2O: 0wt%; Sb2O3: 0.6wt%.
[0054] Example 7
[0055] Example 7 is basically the same as Example 1, except that the raw materials include: Li2O: 12wt%; Al2O3: 2wt%; SiO2: 75wt%; ZrO2: 2wt%; P2O5: 5wt%; Na2O: 3wt%; K2O: 1wt%; Sb2O3: 0wt%.
[0056] Example 8
[0057] Example 8 is basically the same as Example 1, except that the raw materials include: Li2O: 14wt%; Al2O3: 12wt%; SiO2: 60wt%; ZrO2: 4wt%; P2O5: 5wt%; Na2O: 3wt%; K2O: 1wt%; Sb2O3: 1wt%.
[0058] Example 9
[0059] Example 9 is basically the same as Example 1, except that the raw materials include: Li2O:
[0060] 7.6wt%; Al2O3: 8wt%; SiO2: 75wt%; ZrO2: 3wt%; P2O5: 5wt%; Na2O: 0wt%; K2O: 1wt%; Sb2O3: 0.4wt%.
[0061] For the glass-ceramics in Examples 1 to 5, various property parameters of each glass-ceramic were measured using conventional techniques. The measurement results are shown in Table 1:
[0062] Table 1 Test results of properties of high-strength transparent microcrystalline glass in Examples 1 to 5
[0063]
[0064]
[0065] The Xrd spectrum of the prepared high-strength transparent microcrystalline glass was measured using a SmartLab9KW X-ray diffractometer produced by Japan's Rigaku Company. Figure 5 1, 2, 3, 4, 5. The Xrd spectra of the glass-ceramics of Examples 1, 2, 3, 4, and 5 show that the main crystalline phases are lithium disilicate, petalite, and lithium metasilicate.
[0066] The crystal morphology of high-strength transparent glass-ceramics was observed using a Regulus 8100 scanning electron microscope produced by Hitachi, Japan. Figure 1 This is a SEM test picture of the glass-ceramics of Example 3. The lithium disilicate crystals are cylindrical crystals that are interlocked to form a plate-like structure.
[0067] The visible light transmittance spectrum of the prepared high-strength transparent microcrystalline glass was measured using the 722S visible spectrophotometer produced by Shanghai Jinghua Company. Figure 3 3 is a visible light transmittance curve of the microcrystalline glass of Examples 1, 2, 3, and 4. The visible light transmittance of the prepared microcrystalline glass is all above 80%.
[0068] The thermal expansion curve of the prepared high-strength transparent glass-ceramics was measured using a DIL402PC thermal expansion instrument from NETZSCH, Germany. Figure 4 is the thermal expansion curve of Example 5. The thermal expansion coefficient of Example 5 is 6.81×10 -6 .
[0069] The base glass is subjected to a differential scanning calorimetry (DSC) test, and the DSC (mW / mg) is plotted against the temperature °C to indicate the crystallization temperature, and then the precursor glass is subjected to a microcrystallization heat treatment. Figure 2 This is the DSC curve diagram of the base glass of Example 3, from which it is determined that the nucleation temperature of the base glass is 550°C and the crystallization temperature is 620°C.
[0070] Figure 6 The Raman spectra of the base glasses of Examples 1, 2, 3, and 4 all show the presence of 950 cm -1 The vibration peaks at indicate that each component has precipitated Li3PO4 crystal nuclei, and lithium metasilicate and lithium disilicate are crystallized by epitaxial growth on the crystal nuclei Li3PO4.
[0071] The above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, so the obvious changes or modifications derived are still within the protection scope of the invention.
Claims
1. A low-lithium, high-strength transparent microcrystalline glass, characterized in that: The raw materials include: Li2O: 7wt%~15wt%, Al2O3: 2wt%~12wt%, SiO2: 60wt%~78wt%, ZrO2: 1wt%~4wt%, P2O5: 1wt%~5wt%, Na2O: 0~1wt%, K2O: 0~3wt%; Sb2O3: 0wt%~0.6wt%.
2. The low-lithium, high-strength transparent microcrystalline glass according to claim 1, characterized in that: The components Na2O+K2O in the raw materials are>0.5wt%.
3. The low-lithium, high-strength transparent microcrystalline glass according to claim 1, characterized in that: The components Li2O in the raw materials account for 7wt% to 13wt%, Al2O3 account for 5wt% to 8wt%, and SiO2 account for 70wt% to 78wt%.
4. The low-lithium, high-strength transparent microcrystalline glass according to claim 1, characterized in that: The components P2O5+ZrO2 in the raw material are less than 7wt%.
5. The low-lithium, high-strength transparent microcrystalline glass according to claim 1, characterized in that: For samples with a thickness of 1 to 2 mm, the transmittance is at least 88% within the wavelength range of 450 nm to 800 nm.
6. The low-lithium, high-strength transparent microcrystalline glass according to claim 1, characterized in that: For samples with a thickness of 1 to 2 mm, the haze is no more than 0.3%.
7. The low-lithium, high-strength transparent microcrystalline glass according to claim 1, characterized in that: Crystallinity>85%, Vickers hardness≥840kgf / mm 2 , elastic modulus ≥ 100GPa, fracture toughness ≥ 1.1MPa·m 1 / 2 .
8. A method for preparing low-lithium high-strength transparent microcrystalline glass according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1: weigh all raw materials for melting transparent glass-ceramics according to the mass ratio and mix them evenly; Step 2: Put the mixed material obtained in step 1 into a platinum crucible, heat and melt it in a muffle furnace, and after it is fully melted and clarified, pour the obtained melt into an iron mold, then transfer it to an annealing furnace for annealing treatment and cool it with the furnace, and the obtained basic glass sample is stored and used for standby; Step 3: Grind part of the sample in step 2 into powder, perform DSC test, and obtain the crystallization temperature; Step 4: Place the base glass from step 2 in a furnace, cover it with alumina or silica powder for crystallization, and after the crystallization is completed, cool it to room temperature with the furnace to obtain high-strength transparent microcrystalline glass.
9. The method for preparing low-lithium high-strength transparent microcrystalline glass according to claim 8, characterized in that: The melting temperature in step 2 is set to 1450°C and the melting time is set to 2h; The annealing temperature is 520° C. and the annealing time is 30 minutes.
10. The method for preparing low-lithium high-strength transparent microcrystalline glass according to claim 8, characterized in that: The crystallization process described in step 4 is: crystallization at a temperature of 550° C. for 60 minutes, and then crystallization at a temperature of 620° C. for 120 minutes.
Citation Information
Cited By
Glass ceramic, preparation method thereof, electronic equipment cover plate prepared from glass ceramic and electronic equipment cover plate assembly
CN120736800A
Glass ceramic ingot and preparation method thereof, glass ceramic, cover plate glass and electronic equipment
CN122059612A